Lao PDR : Trade and Transport Facilitation Assessment - World Bank (Washington, DC, 2014)
In Lao People's Democratic Republic (PDR), the value of trade has risen rapidly over the last decade with both imports and exports increasing by average annual rate of 24 percent. This report examines the trade logistics of Lao PDR. A trade and transport facilitation assessment was performed using a standardized toolkit and methodology developed by the World Bank to evaluate the quality of the logistics services. The assessment focused on the services used by these trades and the corridors used by these services. The assessment gave specific attention to two constraints on trade, the location of the country and the size of the trade. The study is organized in three interrelated parts: assessing the performance of the logistics sector; the international trade corridors linking Lao PDR to trade gateways in Thailand; and the supply chains used for distribution of exports. This report is presented in four sections. The first part examines the foreign trade of Lao PDR, the opportunities for growth and the logistics services in the movement of imports and exports between the country and its major gateways. The second section evaluates the performance of the corridors connecting the major origins and destinations in the country and the principal seaport used for international trade. The third section analyses the structure and performance characteristics of the supply chains used for selected trades and the implications for restructuring to support growth in the export trade. The final section presents a series of recommendations for improving the competitiveness of the exports through improvements in the structure of the supply chains, the logistics services used by these supply chains, and the corridors used by these supply chains.